Erozija religioznosti v slovenskem javnem mnenju in med študent(kam)i socialnega dela - Dragoš, Srečo (Socialno delo, 2020)
The Slovenian public opinion is very critical of the Roman Catholic Church in Slovenia, ever since the birth of the country a quarter of a century ago. There are several reasons for this situation, but the historical one is by no means decisive. In Slovenia, the Roman Catholic Church is the one who should evangelize, and not society, nor believers, the number of which has recently slightly increased. There is nothing to show that Slovene clerics understand what is happening. The Slovene society - including the Catholic majority of its citizens - is strongly prosocialist and anti-capitalist oriented, and strongly favors greater egalitarianism; according to these characteristics, Slovenia is above the European average and the first among the former socialist countries. It should be emphasized that the category of religious people expresses even greater adherence to socialist values and greater resilience to neoliberalism than is characteristic of the category of unbelievers (including declared atheists). These trends in public opinion are even more pronounced in the student population of the Faculty of Social Work in Ljubljana. It is even more secularized than the Slovene public (according to the criteria for the departure from institutionalized religious practice and dogmatics), but at the same time it shows greater loyalty in relation to the posthumous life and miracles. This is not a contradiction, but one of the characteristics of secularization processes.
Keywords: ateizem; atheism; cerkev; church; ethics; etika; faith; religija; religion; secularization; sekularizacija; vera